Recalibrating disability towards the term subaltern. The social work of neoliberal-academic-ableism in Danish higher education - Tine Fristrup; Christopher Karanja Odgaard (Social Work and Society, 2023)
This paper explores ways in which disabled academics emerge through the social work of what we call neoliberal-academic-ableism in Danish higher education when disability is recalibrated towards the term subaltern. Following Spivak's gendered and racialised subaltern, we are pushed to probe for new interconnected intersections of different formations concerning voicing, speaking, and listening in Danish higher education in general and in the social work support system in particular. Inaugurating our inquiry into academic dis/ability through Spivak's lens of the subaltern, we seek to broaden the scope of Spivak's critical analytical perspective by acknowledging the highly productive ways in which interdisciplinarity and different forms of minority discourses can be mobilised in creative and complex conversations with critical disability studies, studies in ableism, and studies in academic ableism. Our aim is to inform contemporary and future formations of knowledge production about social work and disability in higher education through the framework of neodisability.